First Aid For Accidents Knowledge Level Of Students at Budi Murni 2 Catholic Private High School Medan 2023 - Sara Meilani Sihombing; Indra Hizkia P., S.Kep., Ns., M.Kep; Floresta Br Sitepu, S. Kep, Ns, .M.Psi (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
First Aid in Accidents is a program designed to provide emergency care and treatment to accident victims before they are taken to a hospital, health facility, or clinic where they can receive further medical care from a doctor or paramedic. If an accident or injury is not handled properly, it can develop into an emergency, resulting in serious injury and even death. First aid training and knowledge is very important for dealing with accidents because it teaches basic methods for saving victims from accidents and disasters that occur. This is so that with adequate preparation, such as basic life support training, reaction actions will be faster and more accurate, minimizing the number of victims and damage. The study's goal is to ascertain how "an overview of The degree of student understanding of first aid for emergencies at Budi Murni 2 Catholic Private High School Medan 2023 Purposive sampling was used in this study's descriptive design, with a total of 60 respondents. A questionnaire sheet is the tool that is being used, random sampling. The findings indicate that 96.7% of pupils have first aid knowledge for accidents, knowledge based on fainting was 80%, knowledge based on bleeding are 88.3%, based on broken bones 85%, and knowledge based on splint dressing is 58.3%. It is anticipated that students would become more knowledgeable about and capable of using first aid in accidents.